To be removed or not to be removed: a lexical examination of the soil subsidy debate in Nigeria - Osoba, Gabriel A.; Inya, Faithful (Faculty of Social Sciences and Humanities, UKM,Bangi, 2013)
Whether oil subsidy should be removed or not has been a controversial issue in Nigeria, generating much heat but perhaps least light. This paper makes an attempt to examine the lexical features of selected online contributions on the oil subsidy debate, between October 2011 and February 2012, using a combination of approaches:Computational Stylistics, Stylometry and Critical Stylistics. The study aims at revealing the frequencies of keywords in the oil subsidy debate and providing a comparison of close correspondences between words and their contextual implications. Data for the study are provided by twenty-one (21) selected online articles in Nigerian newspapers on the oil subsidy debate. The lexical investigation reveals that majority opinion favours non – removal of oil subsidy. In other words, oil subsidy should stay.